Long‐term cognitive and motor decline across the spectrum of Lewy body disease. (31st December 2021) - Gonzalez, Maria Camila; Maple‐Grødem, Jodi; Tovar, Diego; Williams‐Gray, Caroline H.; Camacho, Marta; Forsgren, Lars; Bäckström, David; Lawson, Rachael A; Macleod, Angus D.; Counsell, Carl E.; Paquet, Claire; Falup‐Pecurariu, Cristian; et al.
Abstract: Background: This study aims to compare the progression of motor and cognitive decline in dementia with Lewy bodies (DLB) compared with Parkinson's disease (PD) using a large multicentre international consortium with up to 15 years of follow‐up. Method: Longitudinal data from 12 cohorts of patients with PD and DLB were included. The PD cohort (n=1108) included newly diagnosed patients from large, on‐going studies. The DLB cohort (n=290) included patients with probable DLB from the European DLB consortium (Table 1). The Mini Mental State Examination (MMSE) was used to explore cognitive functioning and UPDRS‐III for motor impairment. The differences in the rate of progression of MMSE and UPDRS‐III were analyzed with Linear Mixed Effects Model (LMEM) adjusted for baseline variables, with interactions for time. We used square root transformation of the number of errors to obtain an MMSE variable with normal distribution. Result: Both DLB and PD groups presented motor and cognitive decline. The MMSE (figure 1A) showed a mean annual worsening of 2.35 points (95% CI 1.67‐3.03) for DLB patients and 1.05 points (95% CI 0.62‐1.47) for PD patients (P <0.001 ). In PD the rate of decline increased with time and from the tenth year, the annual rate of decline of the transformed MMSE scores matched the rate in the DLB group. While DLB patients had lower UPDRS‐III scores at baseline, the rate of decline in UPDRS‐III (figure 1B) scores was faster in DLB compared to PD (P <0.001 ). The annual increase in UPDRS III in DLB was 5.8 points (95% CI 5.71‐5.90), while in PD it was 1.9 points (95% CI 1.76‐1.97). Conclusion: Our findings suggest that patients with DLB experience not only more rapid cognitive decline, but also accelerated motor deterioration compared to patients with PD. After ten years of follow‐up (and 12.9 years from the onset of symptoms), PD patients reach DLB's degree of yearly cognitive decline. This is the first large study to compare the natural history of PD and DLB and provides important information about the prognosis of these diseases.